Response to treatment following recently acquired hepatitis C virus infection in a multicentre collaborative cohort. Issue 12 (22nd June 2015) - Doyle, J. S.; Deterding, K.; Grebely, J.; Wedemeyer, H.; Sacks‐Davis, R.; Spelman, T.; Matthews, G.; Rice, T. M.; Morris, M. D.; McGovern, B. H.; Kim, A. Y.; Bruneau, J.; et al.
Summary Pegylated interferon therapy is highly effective in recently acquired HCV. The optimal timing of treatment, regimen and influence of host factors remains unclear. We aimed to measure sustained virological response (SVR) during recent HCV infection and identify predictors of response. Data were from five prospective cohorts of high‐risk individuals in Australia, Canada, Germany and the United States. Individuals with acute or early chronic HCV who commenced pegylated interferon therapy were included. The main outcome was SVR, and predictors were assessed using logistic regression. Among 516 with documented recent HCV infection, 237 were treated (pegylated interferon n = 161; pegylated interferon/ribavirin n = 76) (30% female, median age 35 years, 56% ever injected drugs, median duration of infection 6.2 months). Sixteen per cent (n = 38) were HIV/HCV co‐infected. SVR among those with HCV mono‐infection was 64% by intention to treat; SVR was 68% among HCV/HIV co‐infection. Independent predictors of SVR in HCV mono‐infection were duration of HCV infection (the odds of SVR declined by 8% per month of infection, aOR 0.92, 95% CI 0.85–0.99, P = 0.033), IFNL4 genotype (adjusted OR 2.27, 95% CI 1.13–4.56, P = 0.021), baseline HCV RNA <400 000 IU/mL (aOR 2.06, 95% CI 1.03–4.12, P = 0.041) and age ≥40 years (vs <30: aOR 2.92, 95% CI 1.31–6.49, P = 0.009), with no difference by drug regimen, HCV genotype, symptomatic infection or gender. The effect of infection duration on odds of SVR was greater among genotype‐1 infection. Interferon‐based HCV treatment is highly effective in recent HCV infection. Duration of infection, IFNL4 genotype and baseline HCV RNA levels can predict virological response and may inform clinical decision‐making.